2018
DOI: 10.3926/ic.1258
|View full text |Cite
|
Sign up to set email alerts
|

Mission statements of universities worldwide: Text mining and visualization

Abstract: Purpose: To conduct a transnational study of universities’ mission statements (MS) through content analysis to identify characteristics related to language (e.g. number of words, the most and least frequently used words) and if those characteristics are related to universities’ location, size, focus, research output, age band and status (i.e. private or public). Design/methodology/approach: Content analysis by using Voyant Tools.Findings: The main results showed: (1) a necessity for self-awareness; (2) an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…The mission and vision must also be current and multifactorial; that is, they must consider different elements that affect the environment in which the ports of the sample operate. These results are consistent with other similar studies identified in the literature (Cortes, 2018;Kemp and Dwyer, 2003;L opez-Morales and Ortega-Ridaura, 2016), where there is no congruence Figure 3.…”
Section: Description and Analysis Of Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The mission and vision must also be current and multifactorial; that is, they must consider different elements that affect the environment in which the ports of the sample operate. These results are consistent with other similar studies identified in the literature (Cortes, 2018;Kemp and Dwyer, 2003;L opez-Morales and Ortega-Ridaura, 2016), where there is no congruence Figure 3.…”
Section: Description and Analysis Of Resultssupporting
confidence: 93%
“…The mission and vision must also be current and multifactorial; that is, they must consider different elements that affect the environment in which the ports of the sample operate. These results are consistent with other similar studies identified in the literature (Cortes, 2018;Kemp and Dwyer, 2003;L opez-Morales and Ortega-Ridaura, 2016), where there is no congruence The main findings indicate that, in Latin America, for the most part, ports do not consider elements of CSR in their missions and visions. This results in a lack of strategic foundations that will implement CSR practices and policies in a planned manner.…”
Section: Description and Analysis Of Resultssupporting
confidence: 90%
“…The high rate of occurrence of the term 'knowledge' in libraries' mission statements (33 of 56) is in keeping with universities' mission, inasmuch as it the third most common conceit found in their statements the world over (Cortés-Sánchez, 2018). In Spain, both 'knowledge' and 'innovation' appear in public universities' mission statements (Arias-Coello et al, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…Institutions also incentivise researchers to publish in Scopus' indexed journals -excessively, in some cases -creating structural problems in the quality of BMA research output in developing countries [92][93][94][95]. The higher betweenness of learn in the bottom 10% JMSs supports its high frequency in the MS of universities worldwide, particularly in the small ones [18].…”
Section: Discussionmentioning
confidence: 99%